Decreased level of endogenous secretory receptor for advanced glycation end-products in diabetes with concomitant hyperlipidemia - Turk, Z; Ljubić, S; Boras, J (Physiological research, 2014)
Endogenous secretory receptor (esRAGE) for advanced glycation end-product (AGE) acts as decoy for AGEs. The AGE-to-esRAGE ratio was hypothesized to be implicated in diabetic vasculopathy. We investigated an association of esRAGE and methylglyoxal-adducts serum level, as well as AGE-to-esRAGE ratio in subpopulation of diabetic patients with or without concomitant hyperlipidemia and macrovascular disease in history. In diabetes with concomitant hyperlipidemia esRAGE was significantly decreased compared to hyperlipidemia with normal glucose metabolism (0.306+/-0.2 vs. 0.367+/-0.1; p=0.019) or diabetes alone (0.306+/-0.2 vs. 0.404+/-0.1; p=0.004). High AGE/esRAGE ratio, found in diabetic patients with hyperlipidemia, pointed to increased production of AGEs and low expression of esRAGE. In multivariable analysis adjusted for several confounding factors, increased AGE/esRAGE ratio was recognized as a high risk for vascular disease outcomes.
Keywords: dospělí; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; Diabetes Mellitus, Type 2; lidé; hyperlipidemie; Receptors, Immunologic; Glycation End Products, Advanced; diabetes mellitus 2. typu; receptory imunologické; Male; Aged; produkty pokročilé glykace; lidé středního věku; senioři; mužské pohlaví; Hyperlipidemias; Middle Aged; Humans